The Role of BK Teachers in Providing Psychological Assistance to Students Who Want to Drop Out of School at SMP Negeri 2 Lempuing Jaya - Amaliyah, Rizki; Merliana (International Journal Scientific and Professional, 2025)
This study aims to examine the role of guidance and counseling teachers in providing psychological assistance to students who show a desire to drop out of school at SMP Negeri 2 Lempuing Jaya. This study uses a qualitative approach with an exploratory case study design on one subject of grade IX students. Interventions are carried out by applying Cognitive Behavioral Therapy (CBT) in stages, starting from psychological assessments, group counseling, to individual counseling sessions using cognitive restructuring techniques and CBT worksheets. The results showed a change in the subjects' mindset and perception of education, but economic pressure remains the main obstacle to the sustainability of behavior change. These findings confirm the importance of integrating psychological interventions with family- and economic-based systemic support to prevent sustainable dropouts.